HOYA NARCISSIFLORA (APOCYNACEAE, ASCLEPIADOIDEAE), A NEW SPECIES FROM BORNEO - Sri Rahayu; Michele Rodda (Reinwardtia, 2017)
RAHAYU, S. & RODDA, M. 2017. Hoya narcissiflora (Apocynaceae, Asclepiadoideae), a new species from Borneo. Reinwardtia 16(1): 11 – 16. — A new species of Hoya from Borneo is described, namely Hoya narcissiflora S. Rahayu & Rodda. The species has thin, non-succulent leaves similar to those of species in the Hoya campanulata Group and shallowly campanulate corolla. It is compared with all other Bornean Hoya species possessing campanulate corollas.